A new model for the aerobic metabolism of yeast allows the detailed analysis of the metabolic regulation during glucose pulse - Kesten Weth, Duygu; Kummer, Ursula; Sahle, Sven; Hübner, Katrin (Biophysical chemistry, 2015)
The onset of aerobic fermentation (the so-called Crabtree effect) in yeast has long been of interest. However, the underlying mechanisms at the metabolic level are not yet fully understood. We developed a detailed kinetic model of the aerobic central metabolism of Saccharomyces cerevisiae comprising glycolysis, TCA cycle and major transport reactions across the mitochondrial membrane to investigate this phenomenon. It is the first one of this extent in the literature. The model is able to reproduce experimental steady state fluxes and time-course behavior after a glucose pulse. Due to the lack of parameter identifiability in the model, we analyze a model ensemble consisting of a set of differently parameterized models for robust findings. The model predicts that the cooperativity of pyruvate decarboxylase with respect to pyruvate and the capacity difference between alcohol dehydrogenase and the pyruvate dehydrogenase bypass play a major role for the onset of the Crabtree effect.
Gesehen am 07.06.2017